Madrasah Principal's Strategy in Improving Student Recruitment Results at State Aliyah Madrasas - Mohzana, Mohzana; Masita, Masita; Adnan, Mohammad; Murcahyanto, Hary; Kulsum, Ummu (Pascasarjana Universitas KH. Abdul Chalim, 2023)
The purpose of this study was to find out 1) the strategy used to improve student recruitment results at MAN 1 Mojokerto and 2) the evaluation carried out by the head of the madrasa in the student recruitment strategy at MAN 1 Mojokerto. This study uses a descriptive qualitative research method, namely describing, explaining, and disclosing the results of research on student recruitment using a case study approach. The techniques used in data collection are observation, interviews, and documentation. The results showed that the strategies used by the head of the madrasa in recruiting new students were of five types, namely: 1) Conducting socialization and promotion 2) Opening the 2 Year SKS program 3) Opening the Religious Excellence program (MA PK) 4) Conducting a selection test 5 ) Opens two registration paths. Meanwhile, after carrying out student recruitment activities, the evaluation carried out by the madrasah was to increase the procurement of facilities and infrastructure so that they could accommodate more students.